DOI: 10.18174/544553
|View full text |Cite
|
Sign up to set email alerts
|

Green Care practices and place-based sustainability transformations : A participatory action-oriented study in Finland

Abstract: Chapter 1 'There is no power for change greater than a community discovering what it cares about' Margaret J. Wheatley (1944 -)This chapter provides an overview of the main topics presented in the thesis, as well as their interconnections and relevance in exploring the empirical case of Green Care practices in Finland. It starts by introducing the debate on sustainability transformations and moves on to explain the importance of place and agency in this study. It then presents the phenomenon of Green Care prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 134 publications
(407 reference statements)
0
7
0
Order By: Relevance
“…Through the process of writing the second half of this article we learnt that is can be difficult to pinpoint exactly what is reciprocal about caring relations. Rather than thinking about how the nonhuman responds to care, perhaps we should be thinking about what conditions we create for nonhuman beings to respond (Moriggi, 2021). We suggest to scholars working on care to think through what is reciprocal about the care relations that they study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the process of writing the second half of this article we learnt that is can be difficult to pinpoint exactly what is reciprocal about caring relations. Rather than thinking about how the nonhuman responds to care, perhaps we should be thinking about what conditions we create for nonhuman beings to respond (Moriggi, 2021). We suggest to scholars working on care to think through what is reciprocal about the care relations that they study.…”
Section: Discussionmentioning
confidence: 99%
“…Theorizing and academically discussing care interactions between humans and non-humans is messy, but essential. We learnt and concluded that care and reciprocity with the soil has the power to teach (Moriggi et al, 2020a;Moriggi, 2021), to question, and transform both practices and theories.…”
Section: Discussionmentioning
confidence: 99%
“…This therefore shows green economy teaching to be embedded more in an actionoriented approach. However, from the findings, actionable green learning needs more upscaling, like the participatory action-oriented study of Green Care in Finland (Moriggi, 2021). More information on the significance of green care practices for processes of place-based sustainability transformations that can be emulated by Kenyan higher education institutions is provided in the study.…”
Section: Action-oriented Green Economy Learning Methodsmentioning
confidence: 99%
“…Transformative researchers have experimented with combining a ToC with other design tools (e.g. Theory U) to counteract its mechanistic side (Moriggi, 2021).…”
Section: Characteristics Of Transformative Researchmentioning
confidence: 99%